Epileptic seizures in patients with COVID-19: A systematic review of early evidences - Roy, B; Banerjee, I (Journal of Biomedical Sciences, 2021)
Background: Global emergence of SARS-CoV-2 surfaced neurological complications amongst the patients. COVID-19 resembles with other coronavirus strains follows a trend of neurological complication, damage and encephalopathy, which entails considerable risks, requires attention for the neurologists. This is, to our knowledge, the first systematic review of the literature to investigate solely to elucidate the seizure spectrum by unfolding epileptogenicity of the SARS CoV-2 and potential pathways of neuroinvasion. Methods: A systematic literature search was performed in PubMed and Embase database following standard guidelines, using specific keywords based on epileptic seizure onset described from December 01, 2019, to July 17, 2020 Results: A total of 17 studies were included ranging from case reports, series of cases, multicentre cross-sectional study with the first-time onset of seizure associated with an epileptic origin. We excavated causes of complex COVID-19 related neurological manifestations, e.g., cerebrovascular diseases, encephalitis, demyelinating lesions, cytokine storm and proposed routes of SARS-CoV-2 entry into the nervous system to understand the mechanism of an epileptic seizure. Conclusion: COVID-19 is a potent neuropathogen which causes the new onset of epileptic seizures should get diagnostic recognition to evade possible deterioration of neurological conditions. However, more shreds of evidence from the future will further elucidate the epileptogenic potential of the pandemic.